2016
DOI: 10.1371/journal.pone.0168602
|View full text |Cite
|
Sign up to set email alerts
|

Attempts to Image the Early Inflammatory Response during Infection with the Lymphatic Filarial Nematode Brugia pahangi in a Mouse Model

Abstract: Helminth parasites remain a major constraint upon human health and well-being in many parts of the world. Treatment of these infections relies upon a very small number of therapeutics, most of which were originally developed for use in animal health. A lack of high throughput screening systems, together with limitations of available animal models, has restricted the development of novel chemotherapeutics. This is particularly so for filarial nematodes, which are long-lived parasites with a complex cycle of dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…IL-5 is important in the immune control of filarial infection ( 27 – 30 ). We and others have shown that Brugia experimental infections stimulate high levels of IL-5 systemic responses ( 18 , 21 , 31 ). IL-5 is a promoter, survival, and chemotactic factor for eosinophils ( 1 , 27 , 32 ).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…IL-5 is important in the immune control of filarial infection ( 27 – 30 ). We and others have shown that Brugia experimental infections stimulate high levels of IL-5 systemic responses ( 18 , 21 , 31 ). IL-5 is a promoter, survival, and chemotactic factor for eosinophils ( 1 , 27 , 32 ).…”
Section: Resultsmentioning
confidence: 93%
“…IL-5 is critical in the regulation of residual eosinophilia and immunity against adult B. malayi in the absence of IL-4R signaling IL-5 is important in the immune control of filarial infection (27)(28)(29)(30). We and others have shown that Brugia experimental infections stimulate high levels of IL-5 systemic responses (18,21,31). IL-5 is a promoter, survival, and chemotactic factor for eosinophils (1,27,32).…”
Section: Il-4ra-independent Immunity To Fecund Adult B Malayi Is Assmentioning
confidence: 98%
“…Even the requirement of lymphatic vessels for migration of Litomosoides sigmodontis , a commonly used rodent model of nonlymphatic filariasis, remains speculative 15,16 . These earliest migratory events in filarial infection are challenging to study due in part to technical shortcomings of genetic manipulations of helminths that impede the use of standard imaging techniques in animals 17 . Consequently, a handful of studies that investigated the postinfection fate of filariae were limited to observations of larval migration in excised tissue 18 , used inflammation as an indirect readout 17 , or were performed entirely in vitro 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The lack of previous reports of using filarial larvae to induce a specific immune response can be partially explained by the technical challenges involved in the genetic modification of filaria. The absence of a free-living stage that could be used to amplify the number of transfected nematodes is a significant obstacle for introducing probes or specific genes such as fluorescent proteins or antigens into parasites 49,50 . Furthermore, sustaining a 6 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, the early stages of infection have not been imaged because filarial labeling is a technically challenging process 49 . Therefore, the presented method of intravital fluorescent labeling of infective larvae may become an indispensable tool for imaging the postinfection fate of filarial and possibly other parasites.…”
Section: Discussionmentioning
confidence: 99%